Efektivitas Muscle Energy Technique dan Ischemic Compression Terhadap Myofascial Pain Syndrome Menurunkan Neck Disability Index - Amelia Putri Ardiani; Iman Santoso (Lembaga Pengembangan Kinerja Dosen, 2025)
Myofascial Pain Syndrome is a common musculoskeletal disorder marked by the presence of hyperirritable trigger points within taut bands of skeletal muscle. One frequently affected area is the upper trapezius, where unmanaged pain can significantly imoair neck mobility and reduce quality of life. The Neck Disability Index is a widely accepted tool for evaluating the functional impact of neck pain. However, more evidence research is needed to determine the comparative effectiveness of different physiotherapy interventions in reducing NDI scores. This study employs a systematic review based on the prisma-p and ultilizing the PICOS structure. Articles were selected from databases including PubMed, Crossref, Web of Science, Medline, ScienceDirect, Elsevier, and IEEE. Results indicate that both ICT and MET stretching are effective in reducing pain and enhancing neck function in patients with MPS. The study concludes that ICT and MET can significantly improve NDI scored, suppporting their use as evidence-based physiotherapy treatment for MPS in the upper trapezius.